Circulating microRNA-133a in Patients With Arterial Hypertension, Hypertensive Heart Disease, and Left Ventricular Diastolic Dysfunction - Koval, Sergiy M.; Snihurska, Iryna O.; Yushko, Kostiantyn O.; Mysnychenko, Olga V.; Penkova, Marina Yu.; Lytvynova, Olga M.; Berezin, Alexander E.; Lytvynov, Vadym S. (Frontiers in Cardiovascular Medicine, 2020)
Aim: The aim of the work was to study the circulating microRNA-133a levels in serum of patients with arterial hypertension (AH), hypertensive heart disease (HHD) and left ventricular (LV) diastolic dysfunction (DD). Materials and Methods: A total of 48 patients with grade 2–3 AH and HHD at the age of 52.23 ± 7.26 were examined. 23 of this patients had LV DD (main group) and 25 patients had normal LV diastolic function (comparison group). The control group consisted of 21 practically healthy individuals of comparable gender and age. Diagnosis of AH and HHD was carried out according to the 2018 ESC/ESH recommendations. LV DD was determined according to the 2016 ASE/EACVI recommendations. Plasma miRNA-133a level was obtained by polymerase chain reaction using the CFX96 Touch System (BioRad), «TaqMan microRNA Assay» and «TaqMan® Universal PCR Master Mix» reagent kits (Thermo Fisher Scientific, USA). Results: It was found that in patients from the main and comparison groups miRNA-133a levels were significantly lower than in practically healthy individuals (0.094 [0.067; 0.147]) relative units and (0.152 [0.092; 0.189]) relative units versus (0.382 [0.198; 0.474]) relative units, p <0.01 and p<0.05, respectively. In all this among patients with AH, HHD and LV DD, miRNA-133a levels were significantly lower than in patients with AH, HHD and normal diastolic function (p<0.05). In the main and comparison groups there was a statistically significant negative relationship between miRNA-133a level and left ventricular mass index (LVMI) (r = -0.40, P <0.01 and r = -0.35, P<0.05, respectively). Conclusions: The data obtained indicate a significant role of decreased microRNA-133a levels in serum of patients with AH in the pathogenesis and development of both HHD and LV DD.